1993
DOI: 10.1590/s0101-81751993000300008
|View full text |Cite
|
Sign up to set email alerts
|

Estádios evolutivos de tripanossomas de Hipostomus punctatus Valenciennes (Osteichthyes, Loricariidae) em infecção natural de Batracobdella gemmata Blanchard (Hirudinea, Glossiphoniidae)

Abstract: ABSTRACf. EVOLUTIVE STAGES OF TRIPANOSOMES OF HIPOS-TOMUS PUNCTATUS VALENCIENNES (OSTEICHTHYES,LORICARJ BRUMPT (1905BRUMPT ( , 1906a atribuiu importância taxonômica ao conhecimento dos vetores e modo de evolução do parasito em sanguessugas, descrevendo novas espécies com base neste critério (BRUMPT, 1906b). ROBERTSON (1910)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Fish with these problems are rejected by middlemen due to their poor prices on the market, which raises an additional environmental concern about where the rejected specimens are released. These leeches act as a vector of the trypanosome parasite (D'Agosto and Serra-Freire, 1993), threatening sustainability due to the transmission of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Fish with these problems are rejected by middlemen due to their poor prices on the market, which raises an additional environmental concern about where the rejected specimens are released. These leeches act as a vector of the trypanosome parasite (D'Agosto and Serra-Freire, 1993), threatening sustainability due to the transmission of disease.…”
Section: Discussionmentioning
confidence: 99%
“…In South America, reports of trypanosomiasis are common in several armored fish species (Eiras et al, 1989;Eiras et al, 1990;D'Agosto and Serra-Freire, 1993;Fujimoto et al, 2013;Lemos and Souto-Padrón, 2014;Lemos et al, 2015;Molina et al, 2016;Corrêa et al, 2016), Petenia kraussii (Grögl et al, 1980), catsharks (Morillas et al, 1987;Silva et al, 2005), and in tuvira (Pádua et al, 2011), highlighting that in all these cases, the hosts are wild fish. The most relevant reports of trypanosomiasis in farmed fish are related to groupers in China (Chong, 2005;Su et al, 2014;Wang et al, 2015), and to our knowledge, only Hamid and Babiker (2011) have reported Trypanosoma infections in cultured Nile tilapia Oreochromis niloticus (Sudan).…”
Section: Introductionmentioning
confidence: 99%